(untitled) - Quinn, Lori (U.S.A., 2003)
This hands-on textbook/workbook teaches readers how to document functional outcomes in a clear, logical progression. Extensive examples and exercises in each chapter highlight the essential points of functional outcomes documentation, designed to help improve client function and reduce disability as well as provide evidence of functional progress for insurance payment and reimbursement. Provides both theoretical foundations and a practical approach to functional outcomes documentation. Presents a top-down perspective on rehabilitation, based on the Nagi disablement model. Numerous examples and exercises in every chapter allow readers to put documentation skills into practice as they learn essential theoretical concepts. An overview of key legal issues related to physical therapy documentation is provided. Functional outcomes documentation in a variety of settings is covered, including acute care, rehabilitation, outpatient, home care, nursing homes, pediatrics, school settings, and group homes. Examples illustrate a range of impairments featuring different client groups that challenge students to consider real-life scenarios.
Keywords: Physical therapy,Physical therapy assistants,Medical protocols,Communication in medicine